Extraintestinal Manifestations Are Common in Obese Patients with Crohn's Disease. Issue 9 (27th June 2017) - Singla, Manish B.; Eickhoff, Christa; Betteridge, John
Abstract : Introduction: Crohn's disease (CD) is a chronic condition associated with the risk of malabsorption. The incidence of obesity worldwide is increasing, and the effect of obesity on patients with CD is unknown. We aim to identify traits related to obesity in a cohort of patients with CD. Methods: We conducted a retrospective study of 209 adult patients with CD. Age, Montreal disease classification, sex, race, duration of disease, erythrocyte sedimentation rate, C-reactive protein levels, physician global assessment, endoscopic appearance, histologic activity, medication use, and body mass index (BMI) were collected about each patient. Results: The mean age was 43.4 ± 14.9 years; 68.9% were white, and 51.7% were male. The mean duration of disease was 11.0 ± 10.6 years. The mean BMI was 26.8 ± 5.7: underweight 7.7%; normal weight 29.3%; overweight 38.0%; and obese 25%. Patients with higher BMI were more likely to have extraintestinal manifestations (EIM) ( P = 0.005) and more likely to have nonarthralgia extraintestinal manifestations ( P = 0.047). There was a linear association between proximal CD and decreasing BMI (underweight 31.3%, normal weight 14.8%, overweight 15.0%, obese 7.7%; P = 0.046). There was no difference in BMI between patients with and without perianal disease ( P = 0.216). Conclusions: Most patients were overweight or obese, which correlates with national population trends. Our data suggest disease location plays a role in weight modulation in patients with CD. Increased extraintestinal manifestations in patients with high BMI suggests that the chronic inflammation associated with obesity may play a role in extraintestinal inflammation.